Development and Usability of the Arabic Language Module “Marhaban” Based on CEFR (A1 & A2 Levels) - Abd Rahman, Rahimah; Alias, Hawa; Zakaria, Muhammad Hafizzudin; Razali, Nurul Wardah Nazifah (SIBAWAYH Arabic Language and Education, 2024)
The Common European Framework of Reference (CEFR) was established as a standardized framework in 1960 with the aim of harmonizing the teaching and evaluation of English language skills across the European Union. The CEFR framework comprehensively integrates four fundamental language skills into the educational process, utilizes language proficiency assessment methods that correspond to distinct proficiency levels, and exhibits flexibility in its application. Consequently, the CEFR is widely accepted and used by numerous countries and educational institutions involved in teaching languages, including those teaching Arabic. Hence, Universiti Sultan Azlan Shah (USAS) has initiated the development of an Arabic language module named "Marhaban," which has been meticulously designed following the guidelines of the CEFR for proficiency levels A1 and A2. This module is developed based on the ADDIE instruction model approach, consisting of a structured series of five consecutive stages: analyzing module requirements, designing the module, developing the module, implementing the module, and evaluating the module. Therefore, this study aims to analyze the usability of the module in teaching and learning Arabic language in USAS. This qualitative study was conducted by analyzing the review data collected from the panel of evaluators for the course, comprising of two Arabic language experts who are native speakers and two Arabic language experts who are non-native speakers. The findings were compiled thematically and reported in descriptive form. The findings indicate that this module aligns with the principles of the CEFR framework, which emphasizes on the acquisition of all four language skills through a diverse range of individual or collaborative activities and exercises. Regarding usability, the study indicates that this module is suitable for teaching and learning Arabic language within the context of USAS. This module possesses significant commercial viability by incorporating a variety of components from the local context into its content. Therefore, this resource can be utilized not only within academic institutions for teaching and learning Arabic, but also by the general public for self-directed Arabic language learning.